Crisis, Inequality and Consumption - a Dutch Perspective - Wahlen, Stefan (Italian Sociological Review, 2016)
Inequalities have been exacerbating in the Netherlands since the economic crisis hit ground in 2008, with poverty increasing substantially. The amount of the Dutch population living under the poverty line increased from 7,4 % in 2010 to 10,3 % in 2013. Different types of household are affected: single parent and one-person households, as well as those with migration background. Moreover, life course influences are inherent in the rising amount of children and of elderly in poverty. The aim of this paper is to provide empirical evidence on how new inequalities impact the consumption of food, housing and mobility. Inequalities in food consumption are manifested in the growing amount of food packages handed out by foodbanks increased by 30 % (2012-2013). Housing cost makes up a substantial share of the total expenditure for consumers with lower income and social inequalities become visible in the increasing late payments on mortgages as well as on energy and water consumption. Mobility is of interest, because low-income households appear to cut expenditure on mobility, considering the proportion low-income households spent on mobility is lower as households above the poverty line (7 and 11 % respectively). This paper sheds empirical light on consumption inequalities by providing quantitative empirical evidence. A combination of statistical data is analysed. Life-course influences thereby indicate different peculiarities of consumption inequalities in the types of households affected by poverty.